Makna Islam Damai pada Kanal Youtube @Ustadzah Halimah Alaydrus - Faza Izzatul Haqiqiyah (Proceedings of Student Symposium on Ushuluddin and Islamic Thought, 2024)
This research has a high urgency in studying the development of technology and social media which have made it easier for preachers to spread religious messages, such as morals, aqidah and monotheism. One topic that is often raised is the importance of creating peace in society. The aim of this research is to understand the meaning of peaceful Islam according to Ustadzah Halimah Alaydrus through her YouTube channel. This research is a type of digital research using a content analysis approach. Data sources come from documentation, online data, as well as observations on YouTube and Ustadzah Halimah Alaydrus’ website, which were then researched using several theories from various writers or experts about Islam and peace and also the values ​​of peace in Islam. The research results show the importance of respecting differences of opinion, having an attitude of tolerance, doing good deeds, and treating fellow humans with respect regardless of degree. The most important thing is to maintain piety to Allah SWT. This is in line with Islamic teachings which emphasize that peace must start from within first, through understanding and practicing monotheism. By cultivating a spirit of peace and piety, individuals will find it easier to face challenges and try to find the best solutions, thus encouraging the creation of harmonization in society..